Successful superselective embolization with n-butyl cyanoacrylate for hemorrhage from superficial femoral artery branches following blunt trauma: Three case reports. Issue 27 (2nd July 2020) - Oh, Chang Hoon; Kim, Yook; Lee, Jung Hwan; Kim, Hong Rye; Go, Seung Je
Abstract: Introduction: In blunt traumatic superficial femoral arterial (SFA) injuries, hemorrhage from the branches without injury to the main artery is rare, but can lead to serious complications, such as compartment syndrome affecting the clinical outcomes. Although open surgical repair has been the standard approach to peripheral vascular injuries, endovascular treatment has become more refined and is now an alternative to open surgery, which potentially involves lower morbidity and mortality rates. However, management of arterial injuries, especially when they involve simple bleeding from small branches of the main artery, can be challenging, and the best treatment options for such injuries remains controversial. Patient concerns: Three cases suffered blunt trauma that resulted in hemorrhage from branches of the SFA. Diagnosis: All patients underwent selective angiography, which demonstrated active extravasation from branches of the SFA. Interventions: All patients were treated using embolization with n -butyl cyanoacrylate (NBCA). Outcomes: A post-embolization angiography demonstrated successful hemostasis, with no complications. Conclusion: Superselective catheterization using a coaxial technique with a 5-F curved catheter and the smallest caliber microcatheter, and using a permanent liquid embolic agent, such as NBCA, increases the success rate of embolization for cases of hemorrhage from SFA branches.